Effect of thickness on the microstructure and morphology of copper alloy castings - M., Nasuha; M. M., Rashidi; A., Hadi; Z., Shayfull (AIP Publishing, 2021)
Nowadays, there are various of copper alloy specification was formulated to fulfilled required engineering application. The wide variety of specification opening the door for researchers in order to find the appropriate combination of processing parameters, in this case the setting of copper alloy metal casting process. In general, the product specification produced from molten metal process is influenced by its alloy microstructure. In this study, the effect of component’s thickness on the microstructure of automotive part has been explored. Different thickness of specimen was selected as the variable parameters and investigation of its effect on microstructure was approached. Element composition was calculated, added and mixed during melting stages. Then the molten metal was let solidified in casting cavity by normal cooling condition. Specimen was selected, cut, prepared and examined by optical and scanning electron microscope. Based on the results, the alloy microstructure consist of alloy dendritic structure is affected by the specimen thickness. The fracture surface reveals a smaller dendritic structure and shape at lower cross section specimen.